2021
DOI: 10.1111/vde.13023
|View full text |Cite
|
Sign up to set email alerts
|

House dust mite‐derived serine protease upregulates gene expression of interleukin‐33 in canine keratinocytes via protease‐activated receptor‐2

Abstract: Background -The involvement of interleukin (IL)-33 produced by keratinocytes has been suggested in the pathogenesis of canine atopic dermatitis (cAD). House dust mite (HDM)-derived proteases induce the production of various cytokines and chemokines in keratinocytes via protease-activated receptor-2 (PAR-2); however, their effects on IL-33 mRNA expression in canine keratinocytes have not been determined.Hypothesis/Objective -To clarify whether HDM-derived proteases induce IL-33 mRNA expression in canine keratin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…1 The findings of a recent study suggest that D. farinae-derived serine can upregulate IL-33 mRNA expression in canine progenitor epidermal keratinocytes (CPEK) via protease-activated receptor-2 (PAR-2) activation and may be involved in cAD. 46 Interleukin (IL)-33 produced by keratinocytes is suspected to be involved in the pathogenesis of cAD. 47 Whether these in vitro findings translate into an in vivo situation needs to be proven.…”
Section: House Dust and Storage Mitesmentioning
confidence: 99%
See 1 more Smart Citation
“…1 The findings of a recent study suggest that D. farinae-derived serine can upregulate IL-33 mRNA expression in canine progenitor epidermal keratinocytes (CPEK) via protease-activated receptor-2 (PAR-2) activation and may be involved in cAD. 46 Interleukin (IL)-33 produced by keratinocytes is suspected to be involved in the pathogenesis of cAD. 47 Whether these in vitro findings translate into an in vivo situation needs to be proven.…”
Section: House Dust and Storage Mitesmentioning
confidence: 99%
“…Previous studies indicated that house dust mite (HDM) components, such as cysteine (group 1 mite allergens) and serine (group 3, 6 and 9 allergens) proteases may induce a wide variety of inflammatory reactions, which could promote allergic sensitisation 1 . The findings of a recent study suggest that D. farinae ‐derived serine can upregulate IL‐33 mRNA expression in canine progenitor epidermal keratinocytes (CPEK) via protease‐activated receptor‐2 (PAR‐2) activation and may be involved in cAD 46 . Interleukin (IL)‐33 produced by keratinocytes is suspected to be involved in the pathogenesis of cAD 47 .…”
Section: House Dust and Storage Mitesmentioning
confidence: 99%